ACTUALIZATION OF PANCASILA IN THE MIDDLE OF THE COVID-19 PANDEMIC - Gusti Urpi Anjani; Laila Aska Fariha; Ainur Dewi Khofifah; Handayani Intan Pratiwi; Nur Nila Rosmindiani; Resma Zahra Priandini; Masduki Asbari; Dewiana Novitasari; Agus Purwanto (CV. AGUSPATI RESEARCH INSTITUTA, 2022)
The Coronavirus pandemic is a worldwide pandemic that affects all aspects of life in the world. In Indonesia itself, the Coronavirus Pandemic has changed the habits of Indonesian people who like together and carry out normal activities so that they are forced to be on guard and carry out all activities through trying or advancing. On the one hand, digitization due to the Coronavirus pandemic provides various conveniences but on the other hand, it also saves various obstacles and challenges. These obstacles and challenges are related to how to deal with this Coronavirus pandemic. This article proposes the application of Pancasila values in tackling COVID-19 with the Literature review method with a summary technique that will provide solutions on how to strategy and how to deal with this Coronavirus pandemic by applying Pancasila values which can be the right step to remind the public, Pancasila values must be constructed and applied as a philosophy of life. Therefore, Indonesian citizens should never forget to apply the values of Pancasila in the life of the nation and state to cope with the COVID-19 pandemic.This community service is carried out using lectures and discussions at the media zoom meeting. The number of participants who attended ± people consisted of high school students of economics and the general public.Community service activities with the theme “actualization of Pancasila in the middle of the covid -19 pandemic by looking at divine values, social values and family values.